A Comparative Study of Mental Health of Among Internet Addicted and Non-Addicted Adolescents - Hiral V. Desai (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2020)
Adolescence is the too much sensitive age of life. Mental Health is a vital component of any healthy human life. Internet uses sometimes converts into addiction for adolescent. In the present study researcher selected 120 adolescents selected (30 male internet adolescents, 30 female internet addicted adolescent, 30 male non-internet adolescents, 30 female non-internet addicted adolescent) by purposive sampling technique. Researcher has used Internet Addiction Test by Dr. Kimberly Young was used; and for assess mental health, Mental Health Battery (2013 and revised in 2017) developed by A. K. Singh and Alpana Sen Gupta for collect the data. The result shows that the there is significant difference in mental health level in internet addicted and non-addicted adolescents.